2003
DOI: 10.2134/jeq2003.1881
|View full text |Cite
|
Sign up to set email alerts
|

Recycling Soil Nitrate Nitrogen by Amending Agricultural Lands with Oily Food Waste

Abstract: With current agricultural practices the amounts of fertilizer N applied are frequently more than the amounts removed by the crop. Excessive N application may result in short-term accumulation of nitrate nitrogen (NO3-N) in soil, which can easily be leached from the root zone and into the ground water. A management practice suggested for conserving accumulated NO3-N is the application of oily food waste (FOG; fat + oil + greases) to agricultural soils. A two-year field study (1995-1996 and 1996-1997) was conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 28 publications
4
23
0
Order By: Relevance
“…a reduced quantity of easily oxidizable C or available N remained after 21 d, which triggered microbial death and turnover in the broccoli residue-derived N with the used cooking oil treatment. The pattern of N immobilization followed by re-mineralization with cooking oil was consistent with other laboratory (Smith 1974) and field (Rashid and Voroney 2003) studies. If the period of N immobilization coincides with periods of high risk for N losses in the field, a reduction in N losses may result.…”
Section: Net Nitrogen Mineralizationsupporting
confidence: 89%
“…a reduced quantity of easily oxidizable C or available N remained after 21 d, which triggered microbial death and turnover in the broccoli residue-derived N with the used cooking oil treatment. The pattern of N immobilization followed by re-mineralization with cooking oil was consistent with other laboratory (Smith 1974) and field (Rashid and Voroney 2003) studies. If the period of N immobilization coincides with periods of high risk for N losses in the field, a reduction in N losses may result.…”
Section: Net Nitrogen Mineralizationsupporting
confidence: 89%
“…A pattern of N immobilization followed by re-mineralization with used cooking oil or "fat oil grease" amendments has been found in previous laboratory [11] and field [26] research. In the present study, N immobilized in the OCA-oil after broccoli harvest in autumn could have re-mineralized for the subsequent spring wheat plant uptake.…”
Section: Spring Wheat Productionsupporting
confidence: 62%
“…Research has demonstrated that SMN concentrations may be reduced via N immobilization by the applications of wheat straw [19][20][21], yard waste [22][23][24], and oily food waste [16,25,26]. In the aforementioned studies, immobilized N was derived from fertilizers or indigenous SMN.…”
Section: Introductionmentioning
confidence: 99%
“…Leaf greenness is influenced by a number of factors (hybrid, stage of growth and nutrients), but soil N availability most probably has the greatest effect within a field (Blackmer and Schepers 1995). Soil available N (NO 3 -N) was immobilized during the decomposition of FOG and net N immobilization was significantly higher in SFOG amended plots compared to FFOG amended plots (Rashid and Voroney 2003).…”
Section: Resultsmentioning
confidence: 99%